Diazoxide during pregnancy and lactation: drug levels in maternal serum, cord blood, breast milk, and infant serum: a case report. (3rd June 2022) - Saito, Jumpei; Kawasaki, Hiroyo; Adachi, Natsuho; Sasaki, Aiko; Yakuwa, Naho; Suzuki, Tomo; Sago, Haruhiko; Yamatani, Akimasa; Horikawa, Reiko; Murashima, Atsuko
Abstract: Safety information on diazoxide for pregnant and lactating women with hypoglycemia is limited. In this case report, we assessed diazoxide concentrations in maternal and infant blood, cord blood, and breast milk. We described a 30-year-old pregnant woman diagnosed with hypoglycemia due to nesidioblastosis at 4 months of age. Before becoming pregnant, she was treated with oral diazoxide (75–375 mg). All medications were discontinued after she was discovered to be pregnant. During gestational week 25, diazoxide treatment was resumed at 150–175 mg daily for repeated hypoglycemic episodes. Diazoxide administration was continued in combination with diet treatment until delivery. Glucose levels were well controlled. During gestational week 40, a male infant weighing 3069 g was delivered via spontaneous vaginal delivery with no pregnancy or neonatal complications. Diazoxide concentrations detected in maternal serum at 2.5–11.6 h after oral treatment ranged from 12.4 to 32.7 µg/mL. In cord blood, the diazoxide concentration was 18.5 µg/mL at 7.2 h after the last dose. During lactation, no hypoglycemia or hyperglycemia was observed. The approximate calculated ratio of diazoxide in breast milk and maternal serum was 0.09. The calculated daily infant dose was 0.47 mg/kg/day. The relative infant dose via breast milk ranged from 3.1% to 5.9%. Diazoxide transferred from maternal blood to the fetus across the placenta. It also transferred into breast milk, but there were no harmful effects on the infant.